ANALISIS PENGENDALIAN INTERN PADA SISTEM PERSEDIAAN BARANG DAGANG (STUDI KASUS ROWN DIVISION DI SURAKARTA) - Angela Veda Puspitasari; Setyani Sri Haryani (STIE AUB Surakarta, 2018)
The objectives of this research are to get clear description and to know the effectiveness of internal controlling system of merchandise inventory in Rown Division Surakarta. Merchandise inventory controlling is very important to protect the assets of the company from any corruption, improvidence, and stealing action that might happen and be done by the staffs themselves or any other party. The research method used is descriptive method by doing interview to the warehouse and sales staffs. In this research, the data used is primary data. The researcher gets the data from interview and observing. The result of the research to Rown Division Surakarta shows that their internal controlling is on the right track, because they have applied the elements of internal controlling and the procedures for inventory controlling, that are inventory reception, cash selling, credit selling, and inventory counting.Keyword: analysis, internal controlling, inventory merchandise